PENCIPTAAN BUKU ILUSTRASI PENCAK SILAT UNTUK ANAK-ANAK USIA 6-9 TAHUN SEBAGAI UPAYA PENGENALAN WARISAN BUDAYA BANGSA - Natassia, Naomi; Fianto, Achmad Yanu Alif; Yosep, Sigit Prayitno (Jurnal Art Nouveau, 2015)
Abstract: The aim of this study was to the creation of book illustration martial arts as a national heritage recognition by introducing martial arts as typical Indonesian martial art. Pencak Silat at this time almost replaced with martial arts outside of the more modern. This is mainly because of the rapid developments in technology and communications that support various types of martial arts can easily enter Indonesia and therefore the martial arts today is quite old-fashioned among young people of the nation. So it is not little children today who prefer to learn martial arts outside of the martial arts in the country. Though martial arts in the country is also part of the culture and art that must be preserved and has a lot of positive values that are good for the development of personality and especially children. Martial arts are intimately connected with the development of personality, social, emotional, and motor development of children.Â Keywords: Pencak Silat, Illustration Book, Introduction, History.